Surface Functionalization of Exposed Core Glass Optical Fiber for Metal Ion Sensing - Akash Bachhuka; Sabrina Heng; Krasimir Vasilev; Roman Kostecki; Andrew Abell; Heike Ebendorff-Heidepriem (Sensors, 2019)
One of the biggest challenges associated with exposed core glass optical fiber-based sensing is the availability of techniques that can be used to generate reproducible, homogeneous and stable surface coating. We report a one step, solvent free method for surface functionalization of exposed core glass optical fiber that allows achieving binding of fluorophore of choice for metal ion sensing. The plasma polymerization-based method yielded a homogeneous, reproducible and stable coating, enabling high sensitivity aluminium ion sensing. The sensing platform reported in this manuscript is versatile and can be used to bind different sensing molecules opening new avenues for optical fiber-based sensing.